Optimasi Proporsi Karagenan dan Karakteristik Sensoris Serta Nilai Proksimat Nugget Ikan Mujair dengan RSM - Jusman, Jusman; Syamsuddin, Syamsuddin; Inri EGT (Yayasan Literasi Sains Indonesia, 2024)
This study aims to determine the optimal proportion of carrageenan to enhance the sensory characteristics and proximate values of tilapia (Oreochromis mossambicus) nuggets using the Response Surface Methodology (RSM) approach. Carrageenan concentrations were varied between 0.5% and 2% to evaluate their impact on color, aroma, flavor, texture, as well as protein, fat, and carbohydrate content. The analysis revealed that the optimal carrageenan proportion was 1.25%, with the highest sensory scores: color (9.9), aroma (9.8), flavor (9.9), and texture (9.9). At this level, the nuggets contained 16% protein, 8.5% fat, and 14% carbohydrates. Increasing the carrageenan proportion beyond 1.25% resulted in a decline in sensory quality and nutritional composition. Nuggets with the optimal carrageenan level achieved a balance between desirable texture and nutritional content, making them an ideal choice for fish-based food products. The RSM method proved effective in identifying the best formulation by analyzing variable interactions, ensuring accurate and replicable results. This study provides practical guidance for developing high-quality fish nuggets utilizing carrageenan as a binding agent. The findings are relevant to the food industry in formulating products that are not only flavorful but also nutritionally balanced. Therefore, the 1.25% carrageenan formulation is recommended for commercial applications, with the potential for further development in future research.